Primary Duodenal Signet Ring Cell Carcinoma Presenting as Gastric Outlet Obstruction - López-García, Luis J.; Ojeda, Algia; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2009)
Small bowel tumors occur rarely. We present an unusual case of a 68 year old man with gastric outlet obstruction secondary to a non-ampullary primary duodenal signet ring cell carcinoma. A review of the literature of small bowel malignant tumors is presented along with the case.